TABEL HIDUP Sitophilus oryzae (Coleoptera; Curculionidae) PADA BERAS - Manueke, Jusuf; Tulung, Max; Pinontoan, Odi R.; Paat, Frangky J. (Universitas Sam Ratulangi, 2012)
ABSTRACT The problem in postharvest pests must be handled seriously since recent research were not comprehensively resolved it. Sitophilus oryzae was a major pest and serious problem on post harvest products. The reseach aimed to develop a life table of S. oryzae on rice. The life table is a part of life history that consists of important information about the living organism. This information can be used for predicting population growth. By developing life table database, information on mortality, life expectancy, and the development ability of S. oryzae can be obtained. Results showed that mortality index of eggs was 0.4; larvae was 0,54, and pupae was 0,32, and adult was 1,0. Life expectancy index of eggs was 1.65; larvae was 1.42; pupae was 1.51 pupae; and adults was 1.0. One female was able to give rise 32.56 females or 58.57 males and females of the next generation. Keywords : Life table, Sitophilus oryzae, mortality index, life expectancy